Genetic and Epigenetic Heterogeneity in Normal Liver Homeostasis and Its Implications for Liver Disease and Hepatocellular Cancer - Hlady, Ryan A.; Robertson, Keith D. (Seminars in Liver Disease, 2018)
Hepatocellular carcinoma (HCC) is the most prevalent primary tumor of the liver, and is steadily becoming one of the most lethal cancers worldwide. Liver resection, which is the recommended procedure for early localized HCC, results in frequent recurrence (50–70%), while the standard of care for late-stage HCC, multikinase inhibitors, only improves survival by a few months. The lack of success for these treatment modalities is attributable, at least in part, to marked phenotypic heterogeneity within the tumor. Intratumoral heterogeneity (ITH) has emerged as a defining characteristic of human tumors, with individual cancer cells displaying distinct differences in properties including growth rate, metastatic capacity, and response to treatment. This heterogeneity, which is unlikely to be captured from a biopsy, impacts outcome because a single treatment targeting one cancer-specific pathway would spare tumor cells having distinct characteristics. Development of effective biomarkers remains a major challenge for similar reasons. Understanding, interpreting, and circumventing the impact of ITH is therefore paramount for developing reliable biomarkers and designing effective individualized treatment strategies for HCC.
Keywords: DNA methylation; clonality; ploidy; regeneration; intratumoral heterogeneity